A descriptive report of outcomes of primary mucinous ovarian cancer patients receiving either an adjuvant gynecologic or gastrointestinal chemotherapy regimen. Issue 5 (15th May 2019) - Schlappe, Brooke A; Zhou, Qin C; O'Cearbhaill, Roisin; Iasonos, Alexia; Soslow, Robert A; Abu-Rustum, Nadeem R; Mueller, Jennifer J
Abstract : Objective: We described progression-free survival and overall survival in patients with primary mucinous ovarian cancer receiving adjuvant gynecologic versus gastrointestinal chemotherapy regimens. Methods: We identified all primary mucinous ovarian cancer patients receiving adjuvant gynecologic or gastrointestinal chemotherapy regimens at a single institution from 1994 to 2016. Gynecologic pathologists using strict pathologic/clinical criteria determined diagnosis. Adjuvant therapy was coded as gynecologic or gastrointestinal based on standard agents and schedules. Clinical/pathologic/treatment characteristics were recorded. Wilcoxon rank-sum test was used for continuous variables, and Fisher's exact test for categorical variables. Progression-free and overall survival were calculated using the Kaplan-Meier method, applying landmark analysis. Results: Of 62 patients identified, 21 received adjuvant chemotherapy: 12 gynecologic, 9 gastrointestinal. Median age (in years) at diagnosis: 58 (range 25–68) gynecologic cohort, 38 (range 32–68) gastrointestinal cohort (p=0.13). Median body mass index at first post-operative visit: 25 kg/m 2 (range 18–31) gynecologic cohort, 23 kg/m 2 (range 18–31) gastrointestinal cohort (p=0.23). History of smoking: 6/12 (50%) gynecologic cohort, 3/9 (33%) gastrointestinal cohort (p=0.66). Stage distribution in gynecologic and gastrointestinal cohorts, respectively: stage I: 9/12 (75%) and 3/9 (33%); stage II: 2/12 (17%) and 1/9 (11%); stage III: 1/12 (8%) and 5/9 (56%) (p=0.06). Grade distribution in gynecologic and gastrointestinal cohorts, respectively: grade 1: 8/12 (67%) and 1/9 (13%); grade 2/3: 4/12 (33%) and 7/9 (88%) (p=0.03). Three-year progression-free survival: 90.9% (95% CI 50.8% to 98.7 %) gynecologic, 53.3% (95% CI 17.7% to 79.6%) gastrointestinal. Three-year overall survival: 90.9% (95% CI 50.8% to 98.7%) gynecologic, 76.2% (95% CI 33.2% to 93.5%) gastrointestinal. Conclusion: Ongoing international collaborative research may further define associations between chemotherapy regimens and survival.